Alginate oligosaccharide-mediated butyrate-HIF-1α axis improves skin aging in mice - Ting Gao; Yixuan Li; Xiaoyu Wang; Fazheng Ren (Elsevier, 2024)
The "gut-skin" axis has been proved and is considered as a novel therapy for the prevention of skin aging. The antioxidant efficacy of oligomannonic acid (MAOS) makes it an intriguing target for use to improve skin aging. The present study further explored whereby MAOS-mediated gut-skin axis balance prevented skin aging in mice. The data indicated the skin aging phenotypes, oxidative stress, skin mitochondrial dysfunction, and intestinal dysbiosis (especially the butyrate and HIF-1α levels decreased) in aging mice. Similarly, fecal microbiota transplantation (FMT) from aging mice rebuild the aging-like phenotypes. Further, we demonstrated MAOS-mediated colonic butyrate-HIF-1α axis homeostasis promoted the entry of butyrate into the skin, upregulated mitophagy level and ultimately improving skin aging via HDAC3/PHD/HIF-1α/mitophagy loop in skin of mice. Overall, our study offered a better insights of the effectiveness of alginate oligosaccharides (AOS), promised to become a personalized targeted therapeutic agents, on gut-skin axis disorder inducing skin aging.